Innovation policy, entrepreneurship, and development: A Finnish view - Otto Toivanen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This article first reviews the economic rationales for innovation policy. It then describes the Finnish innovation policy and policy making environment. The Finnish policy is evaluated from the point of view of fostering entrepreneurship. R&D subsidies, the main tool of Finnish innovation policy, may not be a very effective way of fostering entrepreneurship, compared to R&D tax credits of the type used in the Netherlands and Norway. The main reason for this is that the latter provide support in a more transparent way. The article ends with a discussion of what lessons the Finnish innovation policy offers to developing countries.
Keywords: L53; O25; O28; 330; innovation policy; R&D subsidies; R&D tax credit; developing countries; interim efficiency; market failure; Innovationspolitik; Forschungssubvention; Forschungs- und Technologiepolitik; Steuerbegünstigung; Finnland